Common Aquatic Plants of Lake Okeechobee: Identification, Value, and Management - Kenneth A. Langeland; C. C. Jacono (EDIS)
Aquatic and wetland plants are essential to the ecology of Florida lakes, such as Lake Okeechobee, but they can also pose ecological and water use problems. This 16-page fact sheet provides information about the plants of Lake Okeechobee and outlines the importance of certain plants to the lake, problems caused by some plants, and the methods used to manage plants for the benefit of the entire lake environment. Written by K.A. Langeland and C.C. Jacono, and published by the UF Department of Agronomy, July 2012.